PENINGKATAN KESADARAN SISWA TERHADAP KENAKALAN REMAJA, BULLYING, DAN BAHAYA NARKOTIKA MELALUI PROGRAM PENYULUHAN EDUKATIF DI SMP NEGERI 1 TAMBUN SELATAN - Rafli Fahreza Hilmawan; Agung Listianto, Lailatul Badriah, Tiara Khairunnisa, Vatricya Liani, Aulia Cantika Dewi, Restu Gita (Adiba Aisha Amira, 2026)
Adolescence is a developmental stage that is vulnerable to various environmental influences, including juvenile delinquency, bullying, and drug abuse. Therefore, educational efforts are needed as an early preventive measure. This counseling activity was conducted by students of the Community Service Program (KKN) Group 77 of Bhayangkara Jakarta Raya University in Tambun Village at SMP Negeri 1 Tambun Selatan, targeting 25 representative students from grades VII and VIII. The activity was carried out through the delivery of educational materials on juvenile delinquency, bullying, and the dangers of narcotics, combined with educational games and interactive quizzes. The results showed that participants attended the activity enthusiastically and actively participated in discussions and question-and-answer sessions. In addition, students were able to understand the materials presented and demonstrated increased awareness of the importance of avoiding negative behaviors that could affect their future. The use of educational games and interactive quizzes also helped create a more engaging learning environment and encouraged participant involvement throughout the activity. Therefore, interactive counseling programs can serve as an effective preventive effort to enhance adolescents’ knowledge and awareness of various risky behaviors.